2002
DOI: 10.1002/1521-3773(20020415)41:8<1386::aid-anie1386>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

HIO3 and I2O5: Mild and Selective Alternative Reagents to IBX for the Dehydrogenation of Aldehydes and Ketones

Abstract: Economic and convenient: Iodic acid (1) and iodine pentoxide (2) form complexes 3 and 4, respectively, with DMSO when heated at 80°C for 1 h. The complexes are efficient agents for the dehydrogenation of ketones and aldehydes at 45–65°C. X‐ray crystallographic analysis (see picture) shows that the iodine pentoxide⋅DMSO complex 4 self‐assembles into a remarkable helix in the solid state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Furthermore, these IBX substituents are highly chemoselective and effect smooth dehydrogenations at 45−65 °C in the presence of a variety of sensitive functionalities, including unprotected alcohols. 338 Scheme 138 339 shows an example of using IBX as a mild method of oxidation in a multistep asymmetric synthesis starting from chiral cyclopentenone 481, obtained in 90% overall yield from D-ribofuranose, to afford cephalotaxine 485. 339 Cephalotaxine 485 is the most abundant alkaloid constituent of the Cephalotaxus genera identified to date.…”
Section: Oxidation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these IBX substituents are highly chemoselective and effect smooth dehydrogenations at 45−65 °C in the presence of a variety of sensitive functionalities, including unprotected alcohols. 338 Scheme 138 339 shows an example of using IBX as a mild method of oxidation in a multistep asymmetric synthesis starting from chiral cyclopentenone 481, obtained in 90% overall yield from D-ribofuranose, to afford cephalotaxine 485. 339 Cephalotaxine 485 is the most abundant alkaloid constituent of the Cephalotaxus genera identified to date.…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…The authors also demonstrated that HIO 3 and its anhydride I 2 O 5 were more atom-efficient and safer alternatives to IBX for the dehydrogenation of carbonyl compounds. Furthermore, these IBX substituents are highly chemoselective and effect smooth dehydrogenations at 45–65 °C in the presence of a variety of sensitive functionalities, including unprotected alcohols Scheme shows an example of using IBX as a mild method of oxidation in a multistep asymmetric synthesis starting from chiral cyclopentenone 481 , obtained in 90% overall yield from d -ribofuranose, to afford cephalotaxine 485 …”
Section: Asymmetric Functionalization Of Existing Cyclopentenone Unitsmentioning
confidence: 99%
“…As shown in Scheme , hydrogenation of the C–C double bond of 23a in the presence of Pd/C in a hydrogen atmosphere (1 atm) provided product 24a in 81% yield. Unfortunately, several methods to build the enone moiety were investigated, including Saegusa oxidation, selenylation, 2-iodoxybenzoic acid (IBX) oxidation, and Stahl’s palladium-catalyzed dehydrogenation, but these conditions failed to generate the desired product 25a , resulting in decomposition or no reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, 6,7-dehydrogenation product 19 was produced, and the secondary hydroxy group remained intact (Scheme ). It should be noted that Nicolaou recently reported the C-1–C-2 dehydrogenation of dihydrotestosterone using iodic acid in DMSO . Besides compound 19 , minor quantities of the 3-iodo derivative 20 were also found, a derivative that was readily transformed into the 1,4,6-trienone 21 after 1,8-Diazabicyclo[5.4.0]­undec-7-ene (DBU) treatment.…”
Section: Resultsmentioning
confidence: 99%